Comparative Analysis of Tenogenic Gene Expression in Tenocyte-Derived Induced Pluripotent Stem Cells and Bone Marrow-Derived Mesenchymal Stem Cells in Response to Biochemical and Biomechanical Stimuli - Feikun Yang; Dean W. Richardson (Stem Cells International)
The tendon is highly prone to injury, overuse, or age-related degeneration in both humans and horses. Natural healing of injured tendon is poor, and cell-based therapeutic treatment is still a significant clinical challenge. In this study, we extensively investigated the expression of tenogenic genes in equine bone marrow mesenchymal stem cells (BMSCs) and tenocyte-derived induced pluripotent stem cells (teno-iPSCs) stimulated by growth factors (TGF-β3 and BMP12) combined with ectopic expression of tenogenic transcription factor MKX or cyclic uniaxial mechanical stretch. Western blotting revealed that TGF-β3 and BMP12 increased the expression of transcription factors SCX and MKX in both cells, but the tenocyte marker tenomodulin (TNMD) was detected only in BMSCs and upregulated by either inducer. On the other hand, quantitative real-time PCR showed that TGF-β3 increased the expression of EGR1, COL1A2, FMOD, and TNC in BMSCs and SCX, COL1A2, DCN, FMOD, and TNC in teno-iPSCs. BMP12 treatment elevated SCX, MKX, DCN, FMOD, and TNC in teno-iPSCs. Overexpression of MKX increased SCX, DCN, FMOD, and TNC in BMSCs and EGR1, COL1A2, DCN, FMOD, and TNC in teno-iPSCs; TGF-β3 further enhanced TNC in BMSCs. Moreover, mechanical stretch increased SCX, EGR1, DCN, ELN, and TNC in BMSCs and SCX, MKX, EGR1, COL1A2, DCN, FMOD, and TNC in teno-iPSCs; TGF-β3 tended to further elevate SCX, ELN, and TNC in BMSCs and SCX, MKX, COL1A2, DCN, and TNC in teno-iPSCs, while BMP12 further uptrended the expression of SCX and DCN in BMSCs and DCN in teno-iPSCs. Additionally, the aforementioned tenogenic inducers also affected the expression of signaling regulators SMAD7, ETV4, and SIRT1 in BMSCs and teno-iPSCs. Taken together, our data demonstrate that, in respect to the tenocyte-lineage-specific gene expression, BMSCs and teno-iPSCs respond differently to the tenogenic stimuli, which may affect the outcome of their application in tendon repair or regeneration.